Rejoinder to Bagus and Howden on Borrowing Short and Lending Long - Barnett, William T.; Block, Walter 1941- (2011)
In Barnett and Block (J Bus Ethics 88(4):711–716, 2009a), the present authors claim that borrowing short and lending long is fraudulent, and thus ought to be prohibited on legal grounds. Bagus and Howden (J Bus Ethics 90(3):399, 2009) take issue with our ethical analysis. The present paper is our response to these authors; it is an attempt to defend Barnett and Block (J Bus Ethics 88(4):711–716, 2009a) against the very interesting and important, although we believe, erroneous, criticisms of Bagus and Howden (J Bus Ethics 90(3):399, 2009).
Keywords: continuum problem; Natural Law; Fractional reserves; Fraud; Banking